2020
DOI: 10.1038/s41598-020-59261-3
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Morphology Prediction and Anisotropic Evolution of 1,1-Diamino-2,2-dinitroethylene (FOX-7) by Temperature Tuning

Abstract: Temperature-induced morphological changes are one of the strategies for designing crystal shapes, but the role of temperature in enhancing or inhibiting crystal growth is not well understood yet. To meet the requirements of high density and low sensitivity, we need to control the crystal morphology of the energetic materials. We studied the crystal morphology of 1,1-diamino-2,2-dinitroethylene (FOX-7) in dimethyl sulfoxide/water mixed solvent by using the modified Hartman-Perdok theorem. Molecular dynamics sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…According to the Gibbs–Curie–Wulf theorem, the normal growth rate of the crystal face is proportional to the surface free energy . This theory suggests that the (001) surface on the cross section is more active than the ( hk 0) surface along the nanorods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Gibbs–Curie–Wulf theorem, the normal growth rate of the crystal face is proportional to the surface free energy . This theory suggests that the (001) surface on the cross section is more active than the ( hk 0) surface along the nanorods.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Gibbs−Curie−Wulf theorem, the normal growth rate of the crystal face is proportional to the surface free energy. 34 This theory suggests that the (001) surface on the cross section is more active than the (hk0) surface along the nanorods. Thus, in the oxidation of CO, cryptomelane with short nanorods shows higher catalytic activity than that with long nanowires.…”
Section: Reduction Of Manganesementioning
confidence: 99%
“…13,14 It has a symmetrical molecular structure and a wave-shaped π-stacked structure, its energy can be very close to that of RDX, and its sensitivity is close to that of TATB, showing good application prospects in the fields of propellants, explosives and pyrotechnics. 15–18 At present, research studies on FOX-7 mainly focus on theoretical calculations, 19,20 synthesis methods and routes, 21,22 synthetic derivatives, 23,24 and thermal performance studies. 25,26 Some studies on nano-FOX-7 have also been reported, 27–31 and these studies preliminarily show that the morphology, structure and size of nano-FOX-7 have great effects on its performances.…”
Section: Introductionmentioning
confidence: 99%
“…Non-mechanistic (thermodynamic) theories that form the basis of equilibrium morphology prediction have developed drastically since the late 1800's from considering surface energetics, crystal geometry, through to lattice energies and synthonic (intermolecular) interactions. 10,11 Although longestablished, these theories are considered system specific and fail to take into consideration the crystallisation environment Although mechanical breakage is a common occurrence in industrial crystallisers, there exists limited knowledge on the consequent growth of broken crystals. Owing to this, specific post-breakage growth kinetics are rarely accounted for during process modelling, resulting in unreliable predictions of crystal shape and size.…”
mentioning
confidence: 99%
“…Non-mechanistic (thermodynamic) theories that form the basis of equilibrium morphology prediction have developed drastically since the late 1800's from considering surface energetics, crystal geometry, through to lattice energies and synthonic (intermolecular) interactions. 10,11 Although long-established, these theories are considered system specific and fail to take into consideration the crystallisation environment which can radically influence the crystal shape and morphology. 12 As a result, mechanistic (kinetic) models such as the layered growth (spiral growth and Birth & Spread mechanism) and rough growth theories are used to demonstrate that the anisotropic growth of crystal facets depends on the solution properties, solute surface kink density, and the hydrodynamic environment.…”
mentioning
confidence: 99%